Examining teachers’ self-regulation practice in secondary school science teaching: the case of South Gondar Zone, Ethiopia - Mekuriaw Mengistnew (Elsevier, 2021)
The problem of quality education is a burning worldwide issue nowadays. Teachers' teaching quality and effectiveness is one of the major contributing factors for quality education. Self-regulated teaching is becoming the new innovative strategy for quality teaching. Hence, the purpose of this study was to investigate the practice of self-regulated science teaching in the secondary schools of South Gondar Zone of Ethiopia. Nine (9) secondary schools were selected randomly. After selecting the schools, all science teachers, 322 (chemistry, biology and physics) in the selected schools were taken as participants using comprehensive sampling techniques.302/322 = 93.8% (of which 71 (23.5%) were females, 231 (76.5%) were males; 98 = 32.5% chemistry, 100 (33.1%) Biology and 104 (34.4%) Physics) teachers completed the questionnaire. One sample t-test, independent sample test, descriptive statistics and multiple regression analysis were used for data analysis. The findings indicated that there is a positive significant difference between the expected and observed mean of teachers' self-regulated science teaching and it is not by chance. Moreover, teachers are found implementing phase one or preparatory phase (forethought) phase (goal setting, performance goal orientation, mastery goal orientation and intrinsic interest) more than other phases. The study results also showed that there is a significant difference in the implementation of self-regulated science teaching between male and female teachers (females are found better than males). However, gender and teachers' experience together were not found a significant predictor of self-regulated science teaching. The study needs further evidence using observation and interview and the result would have a message for teacher educators to further investigate and adapt in their training manuals to improve teachers’ teaching quality.